Characteristics of the Experimental Study on Assessing the Levels of Proficiency of Student Social Activity in Con ditions of Higher Education Institution - Kulinchenko, O.S.; Vainola, R.Kh. (Наука та інновації, 2019)
Introduction. Nowadays, student self-government is one of the effective forms of student self-organization; it appears to be the mechanism of representing and protecting students’ rights. It is the factor of self-realization and development of social activity in conditions of higher education institution. Problem Statement. The formation of student social activity is a problem of modern pedagogy, since it requires the development of technologies for participating in socially significant activities within the social environment of higher education institutions. Purpose. To characterize and to analyze the stages of the pedagogical experiment regarding the state of the students’ proficiency in terms of social activity. Materials and Methods. A series of diagnostic methods has been used: overt observation, surveys (polls), testing, ranking, moderation method, method of independent expert assessments, a modified version of E. Shakirova’s methodology for diagnosing student social activity, and V. Yadov’s methods. Results. The stages of the assessment of the levels of the formation of student social activity as well as their indicators and criteria have been characterized and analyzed; the socio-pedagogical conditions for the formation of student social activity within the self-government bodies of a higher education institution have been determined: the creation of the structure and bodies of student self-government alongside with the ensuring of the representation of each student groups; the organization of student self-government activities in various fields (organizational, public, research-oriented, physical culture and health-targeted, artistic, creative, educational, informational, and volunteering); the self-organization of students’ life and their involvement into various forms of work performed by self-government bodies; the involvement of teachers into the work of student self-government and promotion of step-by-step formation of student social activity. Conclusions. Currently, students are considered to be not only an intellectual and demographic, but also a spiritual resource of our country. Therefore, social and pedagogical support for the formation and development of indicators of student social activity is a priority task of social and educational work of higher education institutions.